Added value of clinical decision rules for the management of enhancing breast MRI lesions: A systematic comparison of the Kaiser score and the Göttingen score - Dietzel, Matthias; Bernathova, Maria; Clauser, Paola; Kapetas, Panagiotis; Uder, Michael; Baltzer, Pascal A.T. (European Journal of Radiology, 2023)
Purpose: We investigated the added value of two internationally used clinical decision rules in the management of enhancing lesions on breast MRI. Methods: This retrospective, institutional review board approved study included consecutive patients from two different populations. Patients received breast MRI according to the recommendations of the European Society of Breast Imaging (EUSOBI). Initially, all examinations were assessed by expert readers without using clinical decision rules. All lesions rated as category 4 or 5 according to the Breast Imaging Reporting and Data System were histologically confirmed. These lesions were re-evaluated by an expert reader blinded to the histology. He assigned each lesion a Göttingen score (GS) and a Kaiser score (KS) on different occasions. To provide an estimate on inter-reader agreement, a second fellowship-trained reader assessed a subset of these lesions. Subgroup analyses based on lesion type (mass vs. non-mass), size (>1 cm vs. ≤ 1 cm), menopausal status, and significant background parenchymal enhancement were conducted. The areas under the ROC curves (AUCs) for the GS and KS were compared, and the potential to avoid unnecessary biopsies was determined according to previously established cutoffs (KS > 4, GS > 3) Results: 527 lesions in 506 patients were included (mean age: 51.8 years, inter-quartile-range: 43.0–61.0 years). 131/527 lesions were malignant (24.9 %; 95 %-confidence-interval: 21.3–28.8). In all subgroups, the AUCs of the KS (median = 0.91) were higher than those of the GS (median = 0.83). Except for “premenopausal patients” (p = 0.057), these differences were statistically significant (p ≤ 0.01). Kappa agreement was higher for the KS (0.922) than for the GS (0.358). Conclusion: Both the KS and the GS provided added value for the management of enhancing lesions on breast MRI. The KS was superior to the GS in terms of avoiding unnecessary biopsies and showed superior inter-reader agreement; therefore, it may be regarded as the clinical decision rule of choice.
CRIS-Team Scopus Importer:2023-11-17
Keywords: Algorithms; Breast Neoplasms; Clinical Decision-Making; Magnetic Resonance Imaging